PERAN GURU MENGATASI KESULITAN BELAJAR CALISTUNG PADA PESERTA DIDIK KELAS 1B SDS IT SULTHONIYAH SAMBAS TAHUN AJARAN 2023-2024 - Yusrina Yusrina; Suriadi, Eliyah (ADISAM PUBLISHER, 2026)
This research aims to analyze the role of teachers in overcoming difficulties in learning calistung (reading, writing, and arithmetic) for students in grade 1B at SDS IT Sulthoniyah Sambas in the 2023-2024 academic year. The ability to do calistung is a very important foundation for early grade students to be able to follow lessons well. However, it is not uncommon to find students who have difficulties mastering calistung skills. This research uses a qualitative approach with a phenomenological research type. Data collection techniques in this research used interviews, observation, and documentation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The data validity checking techniques used source triangulation and member checking. The results of this study indicate that: (1) The role of teachers in overcoming learning difficulties in 1B grade students includes teacher competencies consisting of pedagogic, personality, professional and social competencies, as well as the role of teachers as mentors, trainers, and researchers. (2) Difficulties in learning calistung for 1B grade students include learning difficulties due to slow student comprehension, low student learning motivation, and low concentration, as well as difficulties in writing with the left hand and often making spelling and reading mistakes even though they have been taught repeatedly. (3) The results of the teacher's role in overcoming calistung learning difficulties for 1B grade students include an increase in students' calistung learning, namely an increase in the number of students who are fluent in reading from 9 to 16 people, showing significant progress in reading skills, and outstanding achievement was shown in arithmetic skills, where all students were able to do arithmetic well in semester 2, and the teacher's level of satisfaction in overcoming calistung learning difficulties still showed 75% because there were still students who had not been successfully guided and taught